1997
DOI: 10.1103/physrevc.55.276
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the linear coupling approximation in heavy-ion fusion reactions at sub-barrier energies

Abstract: The role of higher order coupling of surface vibrations to the relative motion in heavyion fusion reactions at near-barrier energies is investigated. The coupled channels equations are solved to all orders, and also in the linear and the quadratic coupling approximations. Taking 64 Ni + 92,96 Zr reactions as examples, it is shown that all order couplings lead to considerably improved agreement with the experimentally measured fusion cross sections and average angular momenta of the compound nucleus for such he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 35 publications
1
87
1
Order By: Relevance
“…Contrary to the nuclear couplings, the higher order couplings of the Coulomb interaction have been shown to play a rather minor role [6]. The matrix elements are then given by …”
Section: /3mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the nuclear couplings, the higher order couplings of the Coulomb interaction have been shown to play a rather minor role [6]. The matrix elements are then given by …”
Section: /3mentioning
confidence: 99%
“…In the past, the coupledchannels calculations were often performed using the linear coupling approximation, where the coupling potential is expanded in powers of the deformation parameter, keeping only the linear term. It has been demonstrated that non-linear couplings significantly affect the shape of fusion barrier distributions and thus the linear coupling approximation is inadequate in quantitative comparison with the recent high quality data of fusion cross sections [6,7]. The program CCFULL includes the couplings to full order and thus it does not introduce the expansion of the coupling potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to judge the significance of the results because of the limited number of excitations that were included in the C. C. calculations. For example, the only excitation considered in the nickel isotopes is the one-phonon 2 + excitation, but it is well known that couplings to the 3 − state and higher-order couplings to two-phonon states are tremendously enhancing the heavy-ion fusion cross section [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The simplification is achieved by using one or more of the following approximations: i) the linear coupling approximation, where the nuclear coupling potential is assumed to be linear with respect to an excitation operator for intrinsic motions, ii) multi-phonon excitations are neglected, and iii) the eigenchannel approximation, where the intrinsic excitation energies are treated approximately. Since the effective coupling strength is approximately proportional to Z P Z T for a given value of deformation parameter [18], the shortcomings of these approximations become more severe for heavier systems.…”
Section: Coupled-channels Approach To Fusion Of Massive Systems Effecmentioning
confidence: 99%